2020
DOI: 10.1039/c9ce01573f
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pillar size modulation on the magneto-structural coupling in self-assembled BiFeO3–CoFe2O4 heteroepitaxy

Abstract: The magneto-structural coupling of BiFeO3 (BFO)–CoFe2O4 (CFO)/LaAlO3 (LAO) heteroepitaxy with various lateral sizes of CFO pillars embedded in a BFO matrix was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…5(d) can be fitted with three main components: Fe 2+ 2p 3/2 (710.6 eV), Fe 3+ 2p 3/2 (713.1 eV) and Fe 2+ satellite peaks. 19,42 The ratio of Fe 3+ /Fe 2+ is estimated to be about 2.08. As for O 1s core level spectra ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5(d) can be fitted with three main components: Fe 2+ 2p 3/2 (710.6 eV), Fe 3+ 2p 3/2 (713.1 eV) and Fe 2+ satellite peaks. 19,42 The ratio of Fe 3+ /Fe 2+ is estimated to be about 2.08. As for O 1s core level spectra ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16] The present work reports the detailed mechanisms leading to the self-assembled heteroepitaxial growth of the threedimensional (3D) BiFeO 3 -CoFe 2 O 4 (BFO-CFO) VAN on exible mica substrate. Previously, the BFO-CFO VAN grown on various rigid ceramic substrates has been illustrated as multiferroic nanocomposite exhibiting strong magnetoelectric coupling effects, [17][18][19][20] which can bring about profound application potential for next-generation electronic devices in elds such as memory, magnetic sensor, and energy harvesting. It has been recognized that the matrix-pillars conguration of the BFO-CFO VAN was enabled mainly via the surface energy difference between the interface of substrate/perovskite-structured BFO and substrate/spinel-structured CFO.…”
Section: Introductionmentioning
confidence: 99%
“…51,52 Moreover, experiments have also been widely performed to improve the phase distribution morphologies and to enhance the properties of ME VANs. In addition to various piezoelectric and magnetostrictive phase combinations, 16,20,28,[32][33][34][35][36]53 studies (theory and experiments) reveal that the VAN morphology and properties can be controlled by shape and orientations, 3,20,25,54,55 deposition conditions, 19,[56][57][58][59] and substrate constraints. 24,[60][61][62][63]…”
Section: Understanding What Controls Me Vans and Rich Approaches To Adjustments Via Film Growthmentioning
confidence: 99%
“…68 It has been shown that both ME charge and voltage coefficients are significantly larger at large values of r, where the highest values are obtained at magnetic phase fractions of ~ 65% and ~ 93%, respectively. 68 Experimentally, the deposition conditions of epitaxial growth (e.g., target volume fraction, growth temperature, growth rate, and gas pressure for PLD) control the stoichiometry, 56,57 pillar shape, 58 pillar size, 59 and pillar distance. 69 The target volume fraction of perovskite and spinel phases directly determines the stoichiometry of VANs, which further affects their morphologies, and thus the magnetic anisotropy and ME properties.…”
Section: Arrangement Aspect Ratio and Volume Fraction Effectsmentioning
confidence: 99%
See 1 more Smart Citation